KAMPUNG LITERATION PROGRAMME OF KAMPUNG BINA DESA IN SUNGAI KUPAH - Ramadhan, Iwan; Putri, Marbela Vaderofa; Ayuni, Nina; Salsabila, Salsabila; Wartiningsih, Agus; Sanulita, Henny (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The Literacy Village Program implemented by FKIP UNTAN Students in Sungai Kupah Village, Sungai Kakap District, Kubu Raya Regency is a program that fosters a series of new creative, collaborative, and innovative for the cognitive development of children in Sungai Kupah Village. Literacy Village carries several contexts in literacy including reading and writing, science projects, art, and the use of waste into useful items. Implementation of activities with learning and experimental methods. The Literacy Village Program is a means to improve the quality of human resources in the younger generation. The Literacy Village program implemented in Sungai Kupah Village carries several contexts in literacy including reading and writing, science projects, art, and the use of waste into useful items. The existence of literacy programs is expected to provide an improvement in the quality of human resources, especially for the younger generation.